Study of remediation of heavy metals contaminated sediments with hydrothermal technology and sediment washing facilitated by chelating agents - Wong, Angeline Shou Yee. (2013)
This report examines the efficiencies of heavy metals removal of marine sediments by sediment washing and the impact of hydrothermal treatment on heavy metals removal in dredged marine sediments. The targeted heavy metals were Zn, Cu, Pb, Cd, Cr, Ni and As.